Religion and ideology in Assyria - Pongratz-Leisten, Beate (Studies in ancient Near Eastern records ;, 2015)
Addressing the relationship between religion and ideology, and drawing on a range of literary, ritual, and visual sources, Beate Pongratz-Leisten argues that Assyria as a polity was as much exposed to (and influenced by) Babylonia in the south as it was to the Hittite and Hurrian cultural horizon in the north, and that this exposure was clearly reflected in the formulation and development of Assyria's royal ideology.